Information Technology Sector, Women Professionals and Pregnancy Related Issues: A Study With Particular Reference to Kerala. - Cheeran, Maria T. and John, M.S (2012)
Information Technology (IT) industry claims that it is an equal opportunity employer. The present study is intended to find out the merits and demerits of IT career vis-à-vis women especially during the pregnancy period. It is done as a part of a larger study, descriptive cum explorative in nature, to understand the general characteristics of the work environment of IT organization in Kerala, the socio-cultural and familial background of professionals and their family issues related with work. The claim of equal opportunity employment does not seem to agree with the attitude of employers towards pregnant and lactating women. A major portion of women employees was concerned about a standard assessment, chauvinistic to the core, of their male colleagues about their hamstrung performance during pregnancy. Some pragmatic suggestions are proposed to encourage the women professionals‘ chances to continue in the industry after marriage and child birth.